ANALISIS PENGARUH KINERJA KEUANGAN, UKURAN PERUSAHAAN DAN STRUKTUR SUKUK TERHADAP PERINGKAT SUKUK - Bibit Intan Lestari; Mohammad Kholiq Mahfud (Faculty of Economics and Business | Universitas Diponegoro, 2019)
Sukuk rating is something that must be considered by investors when investing in sukuk because sukuk ratings provide information and signals about the probability of the company experiencing default. Sukuk ratings can be influenced by financial factors that are deﬁned by financial performance, firm size and non-financial analysis analyzed by sukuk structure. This study aims to analyze the effect of financial performance as measured by profitability ratios, liquidity, leverage and company size and sukuk structure on sukuk ratings. The population in this study in the non-financial companies that issue sukuk and listed on the Indonesia Stock Exchange (IDX) for the period of 2005-2016, which is still circulating in 2012 - 2017. Sampling in this study uses purposive sampling method, so that the total samples are 13 companies with a total of 57 research data. The data analysis method used in this study is multiple linear regression analysis. From the results of simultaneous multiple regression analysis (Test F) indicate that profitability ratios are proxied by Return On Assets (ROA), liquidity which is proxied by Current Ratio (CR), leverage measured by Debt to Equity Ratio (DER), firm size and sukuk structure in this study shows the F-statistic coefficient value of 16.89648 with a significance value of 0.00000. While based on the results of partial regression analysis (t test) shows that profitability ratios (ROA) and company size (Size) have a positive and significant effect on sukuk ratings. While for the variable liquidity (CR) has a negative and significant on sukuk ratings. Leverage (DER) and sukuk structure does not have an influence on sukuk ratings.